Nickel‐Catalyzed Tandem Knoevenagel Condensation and Intramolecular Direct Arylation: Synthesis of Pyrazolo[5, 1‐a]‐isoquinoline Derivatives. Issue 10 (23rd March 2018) - Dhiman, Shiv; Nandwana, Nitesh Kumar; Saini, Hitesh Kumar; Kumar, Dalip; Rangan, Krishnan; Robertson, Katherine N.; Jha, Mukund; Kumar, Anil
Abstract: A simple and efficient method for the synthesis of pyrazolo[5, 1‐ a ]isoquinoline derivatives has been developed using the nickel‐catalyzed reaction of 1‐aryl‐2‐(1 H ‐pyrazol‐1‐yl)ethan‐1‐ones and 2‐bromo aldehydes. The overall transformation involves tandem Knoevenagel condensation and intramolecular direct arylation via activation of the C5−H bond of the pyrazole ring. A series of 27 drug‐like aroyl−substituted pyrazolo[5, 1‐ a ]isoquinolines has been synthesized in moderate to good yields. Abstract :